Contemporary Conditions for Tourism Sector Transnationalization - USHAKOV, Denis; TSYPKO, Victoria V.; OREHOWSKYI, Vadym O.; VASYLCHUK, Volodymyr M.; KAN, Den Sik (Journal of Environmental Management and Tourism, 2020)
Dynamics of the contemporary stage in transnationalization of tourism and hospitality sectors is predetermined by the specificity of sector’s overall development, its placement in one of the four stages of the sector’s consolidation process which, in its turn, predetermines the national tourism’s capacities to implement efficient strategies of expansion onto foreign markets as well as the rate of tourism sector’s attractiveness for potential foreign investors. The article considers the organizational peculiarities of international M&A processes in the tourism sector and analyzes the instruments used in assessment of their economic efficiency. Different platforms used for mergers and acquisitions in tourist services are discussed. Also, consolidation of tourism industries from different countries is studied as the factor influencing the sectoral dynamics of transnationalization processes.